Assessment of Premenstrual Syndrome among Working Women in Baghdad City - Ikbal M. Abbas, (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To assess the premenstrual syndrome among the working women in Baghdad City.Methodology: A cross-sectional analytic study, using probability sampling cluster (multi-stage) sampling offt°e°*f:£m::?ehL:_ye;roerts:::Ciefdq::d:om|yNfro°v:£°::Cohth°:|o¥dto(3#:th°r3L:Sth2Doa;;WQe::s:j°o[£CateIT:t£T:ufth;::designed and consisted of (4) parts, including demographic, reproductive, menstrual cycle characteristics, andpremeustmual syndrome symptoms. Content validity and reliability of the questionnaire were detemined byconducting a pilot study. Descriptive and inferential statistical procedures were used to analyze the data.Results: The results of the study revealed that the age of women ranged between 30-34 years. The highestpercentage of them was college graduates, most of them was unmarried and most of them was with lowsocioeconomic status. The majority of the study sample had moderate level of premenstnral syndromesymptoms. There were no statistically significant differences between premenstrual syndrome symptoms anddemographic, menstrual cycle characteristics and history of premenstrual syndrome, while there werestatistically significant differences between premenstnral syndrome symptoms and reproductive characteristics.Recommendation: The study recommends to educate women about the premenstrual syndrome symptoms byhealth educational program and reactivate women health clinic to deal with menstrual disorders.